Webbs and Soviet Communism, The : Bolshevism and the British Left Part 2 - Morgan, Kevin, 1961- (Book collections on Project MUSE., 2014)
Through a meticulous reconstruction of the British socialists, economists, and reformers Sidney and Beatrice Webb's way of thinking, this study offers a challenging reassessment of accepted stereotypes, revealing theirs to be a mindset that was far less idiosyncratic than is commonly claimed. Drawing on their diaries, papers, and published writings, this expertly researched critical analysis assesses the couple's complex political evolution over some four decades, artfully illustrating their love affair with Soviet communism.